Mutu Pelayanan Keperawat Berdampak Pada Kepuasan Pasien Di IGD RS Dr. Hafiz Cianjur - Maya Masripah; Sancka Stella; Saiful Gunardi (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Introduction: Nursing services as the front line play a very high role in the satisfaction received by patients One of the determinants of patient satisfaction is the quality of nursing services towards the quality of health services, even becoming one of the determining factors for the image of health service institutions. Objective: to analyze the relationship between the quality of nursing services and patient satisfaction in the Emergency Room of Dr Hafiz Cianjur Hospital Method: The design used is descriptive analytics with a cross-sectional approach The sample taken was 94 respondents using accidental sampling techniques Research data was taken using a questionnaire sheet in October - December 2023. Results: After analyzing the data, it was tabulated using chi square test with a significance level of 005 The research results showed that the Quality of Nursing Services (564%) had 53 respondents in the moderate category and Patient Satisfaction (543%) had 51 respondents in the moderate category The statistical test results obtained a significance value of 0002 Based on the value of p <0005, it can be concluded that there is a relationship between the quality of nursing services and patient satisfaction in the Emergency Room of the Hospital.